Thank you for voting : the maddening, enlightening, inspiring truth about voting in America - Smith, Erin Geiger (Harper, an imprint of HarperCollins Publishers, 2020)
"In this concise, lively look at the past, present, and future of voting, a journalist examines the long and continuing fight for voting equality, why so few Americans today vote, and innovative ways to educate and motivate them; included are checklists of what to do before election day to prepare to vote and encourage others."